Caffeine Restores Neuronal Damage and Inflammatory Response in a Model of Intraventricular Hemorrhage of the Preterm Newborn - Alves-Martinez, Pilar; Atienza-Navarro, Isabel; Vargas-Soria, Maria; Carranza-Naval, Maria Jose; Infante-Garcia, Carmen; Benavente-Fernandez, Isabel; Del Marco, Angel; Lubian-Lopez, Simon; Garcia-Alloza, Monica (Frontiers in Cell and Developmental Biology, 2022)
Germinal matrix-intraventricular hemorrhage (GM-IVH) is the most frequent intracranial hemorrhage in the preterm infant (PT). Long-term GM-IVH associated sequelae include cerebral palsy, sensory and motor impairment, learning disabilities or neuropsychiatric disorders. The societal and health burden associated to GM-IVH is worsened by the fact that there is not successful treatment to limit or reduce brain damage and neurodevelopment disabilities. Caffeine (Caf) is a methylxanthine that binds adenosine receptors, regularly used to treat the apnea of prematurity. While previous studies support the beneficial effects at brain level of Caf in PT, there are no studies that specifically focus on the role of Caf in the GM-IVH. Therefore, to furder understand the role of Caf in GM-IVH, we have analyzed two doses of Caf (10 and 20 mg/kg) in a murine model of the disease. We have analysed the short (P14) and long (P70) effects of the treatment on brain atrophy and neuron wellbeing, including density, curvature and phospho-tau/total tau ratios. We have also analysed, proliferation and neurogenesis as well as microglia and hemorrhage burdens. We have also assessed the long-term effects of Caf treatment at cognitive level. To induce a GM-IVH, we have administered intraventricular collagenase to P7 CD1 mice and we have analyzed these animals in the short (P14) and the long (P70) term. We show a general neuroprotective effect in our model of GM-IVH of the PT. In our hands, Caf administration diminishes brain atrophy and ventricle enlargement. Likewise, Caf limits neuronal damage, including neurite curvature and tau phosphorylation. It also contributes to maintain neurogenesis in the subventricular zone, a neurogenic niche that is severely affected after GM-IVH. Besides, Caf ameliorates small vessel bleeding and inflammation both in the cortex and the subventricular zone. Observed mitigation of brain pathological features commonly associated with GM-IVH, also results in a significant improvement of learning and memory abilities in the long term. Altogether, our data support the promising effects of Caf to reduce central nervous system complications associated to GM-IVH.